Financial literacy and fintech use in family business: Evidence from developing Asia - Wataru Kodama; Peter J. Morgan; Dina Azhgaliyeva; Trinh Quang Long (Asian Development Bank Institute (ADBI), 2024)
A growing literature examines the roles of financial literacy in an individual's income, saving behavior, and the use of financial products including financial technology (fintech). However, no study has examined the effects of the financial literacy of family business owners on fintech use and business outcomes in developing Asia, where family businesses play an important role in the economies. This study investigates these relationships in seven Association of Southeast Asian Nations (ASEAN) and ten Central Asia Regional Economic Cooperation (CAREC) countries. We measured the financial literacy of family business owners using the survey instrument for MSMEs developed by the Organisation for Economic Co-operation and Development and the International Network on Financial Education (OECD/INFE). The results show that self-employed and micro family business owners are less financially literate than owners of larger businesses. We find that a higher level of financial literacy has strong and positive effects on fintech use in family businesses and various business outcomes, including business continuity and changes in sales. These results hold when we use a set of instrumental variables.
Keywords: G50; G51; G53; 330; financial literacy; fintech; family business; Southeast Asia; Central Asia; Caucasus